The culture of Penaeus Indicus Milne Edwards in experimental closed systems with special reference to water quality - Gerhardt, Hedley Vernon (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1979)
This study embraces two aspects of closed system culture: (a) a comparative study of four different biological filtration treatments, and (b) a quantitative determination of the nitrogen flow in a particular biological filtration system. Twenty 0,5 g juvenile Penaeus indicus Milne Edwards were cultured for approximately two months in four different kinds of sea water recirculatory systems with bacterial filtration, algal filtration, algar plus bacterial filtration and water exchange (25% every 3 days). Growth was comparable to that found in the literature for P. indicus. Nitrification occurred in all systems irrespective of the type of biological filtration employed. Ammonia, nitrite and nitrate levels were reduced by the algae, but nitrate accumulated to approximately 30 mg NOÂ¯Â³ -Nâ„“Â¯Â¹ in those systems without algae. Depletion of trace elements (Cu, Fe, Zn, Hn and Co) by the algae did not occur due to trace metal replenishment from the addition of food. No marked changes occurred in the concentrations of the major cations (Caâ ºâ º, Mgâ ºâ º, Naâ º and Kâ º), but a small increase in Caâ ºâ º levels was detectable in those systems with oyster shell chips in the filtration medium. Only minor changes occurred in oxygen or pH values in the various systems tested. Inorganic carbon levels showed major increases in the algal filtration systems, while a slight drop occurred in the bacterial filtration systems. The increase in the algal filtration systems was thought to be due to the formation of carbonates and bicarbonates by the reaction of respiratory COâ‚‚ with unionized ammonia and water. Suggestions are made as to how closed systems can be improved upon. By determining the rate of excretion of P.indicus as related to size and temperature, its faecal production, and the nitrogen content of P.indicus, its food and faeces, the nitrogen flow within a system could be calculated. P.indicus was found to have an assimilation efficiency of 88,93% and a food conversion ratio of 3,49:1. Of the total dietary nitrogen input into the system, P.indicus ingested 69,02% - 19,80% of which was used for growth, 41,58% excreted and 7,64% lost as faeces. The remaining 30,98% of the total nitrogen input can be regarded as excess food nitrogen. The total nitrogen loading on the biological filtration system was found to be 80,20% of the total input of dietary nitrogen. The ability of various types of filamentous algae to remove these nitrogen compounds was determined. Suggestions are made as to the application of this information on nitrogen flow to the culture of P.indicus
Keywords: Penaeus Indicus; Aquatic animals; Water quality